2009
DOI: 10.1002/job.584
|View full text |Cite
|
Sign up to set email alerts
|

Zest and work

Abstract: SummaryZest is a positive trait reflecting a person's approach to life with anticipation, energy, and excitement. In the present study, 9803 currently employed adult respondents to an Internet site completed measures of dispositional zest, orientation to work as a calling, and satisfaction with work and life in general. Across all occupations, zest predicted the stance that work was a calling (r ¼ .39), as well as work satisfaction (r ¼ .46) and general life satisfaction (r ¼ .53). Zest deserves further attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
226
2
13

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(262 citation statements)
references
References 41 publications
21
226
2
13
Order By: Relevance
“…Taken together, these articles demonstrate several important themes and directions for additional research. The first article, by Peterson, Park, Hall, and Seligman (2009) meaningfully extends Peterson and Seligman's (2004) work on character strengths to organizational settings. Focusing on the character strength of zest, which is defined as the habitual approach to life with anticipation and energy, Peterson et al (2009) found that zest was associated with work as a calling, work satisfaction, and general life satisfaction using a sample of 9803 employed respondents to the VIA internet site.…”
Section: Special Issue Articles: Can Positive Research Build Strongermentioning
confidence: 77%
See 1 more Smart Citation
“…Taken together, these articles demonstrate several important themes and directions for additional research. The first article, by Peterson, Park, Hall, and Seligman (2009) meaningfully extends Peterson and Seligman's (2004) work on character strengths to organizational settings. Focusing on the character strength of zest, which is defined as the habitual approach to life with anticipation and energy, Peterson et al (2009) found that zest was associated with work as a calling, work satisfaction, and general life satisfaction using a sample of 9803 employed respondents to the VIA internet site.…”
Section: Special Issue Articles: Can Positive Research Build Strongermentioning
confidence: 77%
“…Of particular relevance to our next article is the character strength of hope. Preliminary analyses by Peterson et al (2009) indicate that a number of their character strengths, such as hope, demonstrate the trait-like quality of a high test-retest correlation, in this case over a 4-month period. Alternatively, based upon the work of Snyder (2000) and Luthans et al (Luthans, Avolio, Avey, & Norman, 2007;Luthans & Youssef, 2007), hope has also been considered as a state.…”
Section: Special Issue Articles: Can Positive Research Build Strongermentioning
confidence: 85%
“…Recent research is also establishing the nomological network around this relatively new construct. This largely cross-sectional research Follow Your Heart 6 has primarily documented positive correlations between calling and subjective constructs such as life and job satisfaction (Duffy, Bott, Allan, Torrey, & Dik, 2012;Peterson, Park, Hall, & Seligman, 2009;Wrzesniewski, McCauley, Rozin, & Schwartz, 1997), intrinsic motivation, work engagement, job involvement (Dobrow & Tosti-Kharas, 2011), zest (Peterson et al, 2009), and well-being (Duffy, Manuel, Borges, & Bott, 2011).…”
Section: Calling and Career Pursuitmentioning
confidence: 99%
“…People with a sense of calling are assumed to express their strengths through their calling and as such should possess high confidence in their ability to master career-related tasks (Hall & Chandler, 2005). Similarly, individuals with a sense of calling are enacting their "true selves" in the work role, which entails expressing their core strengths (Peterson, Park, Hall, & Seligman, 2009). Therefore, although the presence of a calling may not directly translate into a specific level of a person"s objective ability (Dobrow, in press), we could assume that a calling can promote a sense of career self-efficacy.…”
Section: Calling and Career Preparationmentioning
confidence: 99%